Quantifying immediate carbon emissions from El Nino-mediated wildfires in humid tropical forests - Withey, Kieran; Berenguer, Erika; Palmeira, Alessandro Ferraz; Espirito-Santo, Fernando D. B.; Lennox, Gareth D.; Silva, Camila V. J.; Aragao, Luiz E. O. C.; Ferreira, Joice; Franca, Filipe; Malhi, Yadvinder; Rossi, Liana Chesini [UNESP]; Barlow, Jos (Royal Soc, 2018)
Wildfires produce substantial CO2 emissions in the humid tropics during El Nino-mediated extreme droughts, and these emissions are expected to increase in coming decades. Immediate carbon emissions from uncontrolled wildfires in human-modified tropical forests can be considerable owing to high necromass fuel loads. Yet, data on necromass combustion duringwildfires are severely lacking. Here, we evaluated necromass carbon stocks before and after the 2015-2016 El Nino in Amazonian forests distributed along a gradient of prior human disturbance. We then used Landsat-derived burn scars to extrapolate regional immediate wildfire CO2 emissions during the 20152016 El Nino. Before the El Nino, necromass stocks varied significantly with respect to prior disturbance and were largest in undisturbed primary forests (30.2 +/- 2.1 Mg ha(-1), mean +/- s. e.) and smallest in secondary forests (15.6 +/- 3.0 Mg ha(-1)). However, neither prior disturbance nor our proxy of fire intensity (median char height) explained necromass losses due towildfires. In our 6.5 million hectare (6.5 Mha) study region, almost 1 Mha of primary (disturbed and undisturbed) and 20 000 ha of secondary forest burned during the 2015-2016 ElNino. Covering less than 0.2% of Brazilian Amazonia, thesewildfires resulted in expected immediate CO2 emissions of approximately 30 Tg, three to four times greater than comparable estimates fromglobal fire emissions databases. Uncontrolled understoreywildfires in humid tropical forests during extreme droughts are a large and poorly quantified source of CO2 emissions. This article is part of a discussion meeting issue 'The impact of the 2015/2016 El Nino on the terrestrial tropical carbon cycle: patterns, mechanisms and implications'.
Keywords: ENSO; forest degradation; climate change; necromass; drought; Amazon